Exploratory clinical characterization of experimentally-induced ulcerative colitis nonhuman primates. Issue 1 (January 2020) - Takahashi, Nobuyuki; Kitazawa, Chinatsu; Itani, Yoshitaka; Awaga, Yuji; Hama, Aldric; Hayashi, Ikuo; Takamatsu, Hiroyuki
Abstract: A limitation of currently used preclinical models of colitis is that disease and treatment assessment methods differ from clinically used methods. Thus, a modified Mayo score and an endoscopic index (EI) were developed for use in cynomolgus macaques with 0.25% dextran sulfate sodium (DSS)-induced ulcerative colitis. Macaques were treated with water with DSS for two weeks followed by water without DSS for two weeks. Disease activity was classified according to a modified Mayo score: stool consistency, rectal bleeding, colonoscopy examination and global assessment. Findings on colonoscopy were further graded according the Rachmilewitz EI. To demonstrate the sensitivity of the modified Mayo score and EI to therapeutic intervention, macaques were treated with the anti-inflammatory steroid prednisolone followed eight weeks later by the integrin antibody vedolizumab. Before DSS treatment, normal stool consistency and no rectal bleeding were observed. Colonoscopy demonstrated no mucosal abnormalities. Following the first DSS treatment, Mayo score and EI indicated signs of mild colitis. Following subsequent DSS treatments, mild to moderate colitis emerged with each DSS treatment and reduced signs of colitis were observed 2 weeks after DSS treatment termination. Prednisolone treatment during DSS treatment suppressed the emergence of colitis. Vedolizumab reduced signs of colitis during DSS treatment and further reduced signs of colitis that persisted after termination of DSS treatment. The current study demonstrated the potential of utilizing clinical outcome measures to assess experimentally-induced colitis in the macaque. Furthermore, signs of colitis, as assessed with the current methods, were reduced following therapeutic treatment. The current findings suggest that clinically relevant outcome measures in the macaque model of ulcerative colitis could be used to test novel treatments. Abstract : Immunology; Organ system; Gastrointestinal system; Pathology; Pharmacology; Pharmaceutical science; Medical imaging; Preclinical to clinical translation; Macaque model; Vedolizumab; Prednisolone